POTENSI RETRIBUSI PASAR BUNGA RAWABELONG JAKARTA - , Ir. Asep Sutisna; , Dr. Soeratno, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Potential Rertribusi Rawabelong Flower Market, aims to analyze and calculate the potential levies Rawabelong Flower Market, the period 2005-2009. The analysis tools are Growth, Contribution / Share, Effectiveness and Efficiency and the Potential The calculation result contribution / share of market retribution that is during the time period 2005 - 2009 average of 0.05 percent per year, whereas the contribution or the share market retribution against region income over the period 2005 to 2009 indicate a tendency to fluctuate from year to year, ranging from 0.00056 per cent in 2005 has decreased in 2008 amounted to 0.00032 percent, due in that year the only market that operates the south, while north of the market which is being built, then in 2009 an increase of 0.00005 per cent, this is due to start operating north market. Development Levies revenue realization Bungarawabelong Market during the period of observation from 2005 until 2009 which showed growth fluctuated from year 2005 to 2007 an average of 133 percent, while from year 2007 to 2008 growth minus / decreased by 4.84%. from 2008-2009, while growth increased by 4.51 percent. Calculation of the potential market levies in 2009 by performing the sum on the basis of tariff within one year of Rp841.640.000. The average effectiveness of the collecting levies on rawabelong flower market is 36 percent, this shows that on average, less current market levy collection is less effective. The efficiency rate of collection / management market levy during the time period of the fiscal year 2007 to 29,009 in the flower market rawabelong ranged from 738.42 percent to 1028.20 percent and showed a tendency to a fluctuating level of efficiency, namely in the 2007 fiscal year amounted to 738 levels of efficiency , 42 per cent to 1028.20 per cent in 2008, and in 2009 to 975.32 percent, so the low level of efficiency or inefficiency